2013
DOI: 10.5935/0101-2800.20130046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of captopril on peritoneal fibrosis induced in rats by the use of glucose solution 4.25%

Abstract: Our findings indicate that captopril do not decrease the intensity of fibrosis on the peritoneal membrane that happens on rats on peritoneal dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In a subsequent study using the same model, these authors found that the AT1R antagonist valsartan was equal to the ACE inhibitor lisinopril in mitigating peritoneal injury caused by glucose-containing PD fluid (19). In a similar study from another laboratory, PD fluid containing 4.25% glucose was injected into the peritoneal space of rats with normal renal function daily for 3 or 7 weeks, and the ACE inhibitor captopril at 30 mg/kg/d was administered by gavage each day to half of the animals (20). There were trends toward less peritoneal thickness, less cellularity, and less collagen expression in the captopril group, especially in the parietal peritoneum, but statistical significance was not reached.…”
Section: Peritoneal Dialysismentioning
confidence: 99%
“…In a subsequent study using the same model, these authors found that the AT1R antagonist valsartan was equal to the ACE inhibitor lisinopril in mitigating peritoneal injury caused by glucose-containing PD fluid (19). In a similar study from another laboratory, PD fluid containing 4.25% glucose was injected into the peritoneal space of rats with normal renal function daily for 3 or 7 weeks, and the ACE inhibitor captopril at 30 mg/kg/d was administered by gavage each day to half of the animals (20). There were trends toward less peritoneal thickness, less cellularity, and less collagen expression in the captopril group, especially in the parietal peritoneum, but statistical significance was not reached.…”
Section: Peritoneal Dialysismentioning
confidence: 99%